Pregnancy in Patients With Hereditary Angioedema and Normal C1 Inhibitor - Gabriel, Natalia; Marcelino, Fernanda; Ferriani, Mariana P. L.; Arruda, L. Karla; Campos, Regis A.; Gonçalves, Rozana F.; Chong-Neto, Herberto; Rosario Filho, Nelson; Valle, Solange O. R.; Pesquero, Joao B.; Grumach, Anete S. (Frontiers in Allergy, 2022)
Background: HAE with normal C1 inhibitor (HAE-nC1-INH) has been identified as a bradykinin mediated angioedema. Estrogens are one of the main trigger factors. Pregnancy in HAE with C1 inhibitor deficiency showed variable course, however, few reports are available for HAE-nC1-INH. We evaluated the course of pregnancies in women diagnosed with HAE-nC1-INH. Methods: Women with diagnosis of HAE-nC1-INH according to the following criteria: clinical manifestations similar to HAE-C1-INH, normal biochemical evaluation and family history were included. A questionnaire about pregnancies was applied after consent. Genetic evaluation for known mutations was performed in all patients. Results: A total of 45 pregnancies occurring in 26 HAE-nC1-INH patients were evaluated (7/26 patients with F12 variant). Abortion was reported in 8/45 (17.8%) pregnancies. Onset of attacks started before the pregnancy in 18/26 patients; during the pregnancy in 2/26; and after the pregnancy in 6/26. HAE attacks occurred in 24/37 pregnancies (64.7%): during the 1st trimester in 41.7%; 2nd trimester in 12.5%; 3rd trimester in 20.8%; 1st and 3rd trimesters in 4.2% and during the whole pregnancy in 20.8%. Among 15/18 patients who had attacks before pregnancy, symptoms persisted with worsening in 9/15; improvement in 4/15; no change in 1/15, and no response in 1/15. Conclusions: The occurrence of abortion in HAE-nC1-INH was similar to the expected for not affected women. The 1st trimester of the pregnancy was more symptomatic for HAE-nC1-INH women. Considering the strong relevance of estrogens in HAE-nC1-INH, pregnancy could worsen the course of disease.